A106 Spatial Heterogeneity in Associations between Car Commuting and Stress: A Cross-sectional Panel Analysis of Southern Sweden. Issue 2 (June 2015) - Mattisson, Kristoffer; Cromley, Ellen
Abstract: Background: The adverse health effects associated with long commutes provides additional evidence of the commuting paradox. Better job opportunities and higher incomes in larger local labour markets are offset by the negative consequences of longer commutes including lower levels of life satisfaction. Long commutes extend the work day and time spent commuting is time lost for health beneficial activities such as social participation, sleep, and physical activity. Commuters are also exposed to a number of stressors, such as delays, inflexibility of schedules, noise, and pollution. A cross-sectional study conducted in southern Sweden concluded that levels of self-reported stress were higher among people commuting by car and public transit than among active commuters. Most research on health effects of commuting is cross-sectional and summarizes data for entire study communities. The purpose of this study is to investigate spatial heterogeneity in levels of stress over time reported by workers with long car commutes, given the dominance of that mode. Local spatial statistics identify places with higher proportions of stress compared to the county as a whole. Methods: The study population was drawn from a public health survey conducted in 2000 with follow-up in 2005 and 2010. Each of the 997 individuals included in the study was between 18-65 years old at baseline worked 15-60 h per week, commuted 30-60 min by car, reported a valid stress level, and had residential location coordinates in the county in one of more years of the panel. Geographically weighted proportions were calculated for each commuter in the study population for each time period using a fixed bandwidth of 20 km and Gaussian weights to identify areas with high proportions of car commuters reporting stress. For selected areas with high proportions of commuters reporting stress, local proportions of stress in car commuters are compared to proportions for the county as a whole. Results: Levels of stress declined among 30-60 min car commuters over time but were higher in each period than the levels of stress for the panel as a whole. Spatial heterogeneity also decreased over time. At baseline, higher proportions of 30-60 min car commuters reported stress in certain regions, especially in the southwest. By 2010, geographical differences in stress levels diminished, but the area of higher stress was in the north. Conclusions: Spatial methods applied in this study provided important insights into the health effects of commuting and how they change over time.